Sm-Nd and Lu-Hf isotope and trace-element systematics of Mesoarchaean amphibolites, inner Ameralik fjord, southern West Greenland - Szilas, Kristoffer; Hoffmann, J. Elis; Hansmeier, Christina; Hollis, Julie A.; Muenker, Carsten; Viehmann, Sebastian; Kasper, Haino U. (MINERALOGICAL SOC, 2015)
Fragmented supracrustal rocks are typical components of Archaean high-grade gneiss terranes, such as those in the North Atlantic Craton. Here we present the first major, trace element and Nd-Hf isotope data for amphibolites collected in the yet poorly studied southern inner Ameralik fjord region of southern West Greenland. In addition, new U-Pb zircon ages were obtained from the surrounding TTG gneisses. Based on their trace-element patterns, two different groups of amphibolites can be distinguished. Following screening for post-magmatic alteration and outlying epsilon values, a reduced sample set defines a Sm-147/Nd-143 regression age of 3038 Ma +/- 310 Ma (MSWD = 9.2) and a Lu-176/Hf-176 regression age of 2867 +/- 160 Ma (MSWD = 5.5). Initial epsilon Nd-2970Ma values of the least-altered amphibolites range from 0.0 to +5.7 and initial epsilon Hf-2970Ma range from +0.7 to +10.4, indicating significant isotopic heterogeneity of their mantle sources with involvement of depleted domains as well as crustal sources. Surprisingly, the amphibolites which are apparently most evolved and incompatible element-rich have the most depleted Hf-isotope compositions. This apparent paradox may be explained by the sampling of a local mantle source region with ancient previous melt depletion, which was re-enriched by a fluid component during subduction zone volcanism or alternatively by preferential melting of an ancient pyroxenite component in the mantle source of the enriched rocks.